662 Establishing an Acute Extracorporeal Lithotripsy Service in The COVID 19 Pandemic. (12th October 2021) - Theivendrampillai, T; Hart, E; Mahesan, T
Abstract: Introduction: In England, 40% of patients who present with urinary tract stones as an emergency are actively managed with a procedure, in the majority a stent. This commits them to an inpatient stay, a general anaesthetic and further surgery at a later date. Extracorporeal Shockwave Lithotripsy (ESWL) offers a promising, outpatient alternative especially during the COVID19 pandemic. With COVID19 limiting our ability to provide urgent stone care, we assessed our institutions compliance with Getting It Right First Time (GIRFT) guidelines- which recommends that 10% of patients with acute stones undergo ESWL. Method: The audit comprised of 2 cycles; collecting data on the number patients that were admitted with renal colic over a 3-month period, and the percentage treated with ESWL. The first cycle collected data from February to April 2020, while the second cycle collected data from May 2020 to July 2020. Results: The first cycle of the audit revealed that 0 patients were treated with acute ESWL. This required implementation of a referral pathway to Frimley Park Hospital who provided ESWL services. After implementation of a pathway, the 2nd cycle of the audit saw that of 32 patients, 6 patients were referred to Frimley for emergency ESWL (compliance rate: 19%). Conclusions: With the implantation of a referral pathway, the percentage of patients that we referred for ESWL rose significantly from 0% to 19%, thereby meeting GIRFT guidelines. This audit re-iterates how the pandemic has shifted the way we provide urgent stone care with emergency ESWL in our local trust